2007
DOI: 10.1097/mbp.0b013e32813fa386
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Omron M5-I, R5-I and HEM-907 automated blood pressure monitors in elderly individuals according to the International Protocol of the European Society of Hypertension

Abstract: According to the results of the validation study based on the European Society of Hypertension International Protocol the Omron M5-I, R5-I, and HEM-907 may be recommended for clinical use in elderly individuals, without atrial fibrillation or frequent ectopic beats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 29 publications
1
73
0
Order By: Relevance
“…Although statistically significant, these differences are very small and should have little impact in the clinical setting or in epidemiologic studies. Our results are consistent with those of some 10,11 , but not all studies on other Omron devices [12][13][14][15] . We also found that the Omron HEM-705 CP qualifies as a grade A device for measuring blood pressure, according to the BHS protocol criteria 1,2 .…”
Section: Discussionsupporting
confidence: 93%
“…Although statistically significant, these differences are very small and should have little impact in the clinical setting or in epidemiologic studies. Our results are consistent with those of some 10,11 , but not all studies on other Omron devices [12][13][14][15] . We also found that the Omron HEM-705 CP qualifies as a grade A device for measuring blood pressure, according to the BHS protocol criteria 1,2 .…”
Section: Discussionsupporting
confidence: 93%
“…15,16 All of the tonometry data were stored and uploaded via a file transfer protocol mechanism to a central server and reviewed by a single core laboratory member to ensure adequate waveform quality for analysis. Augmentation index was calculated as the ratio of the second and first radial systolic pressure peaks.…”
Section: Radial Artery Tonometrymentioning
confidence: 99%
“…[2][3][4] It has distinct advantages in sub-populations in which automated oscillometric device readings are less accurate, particularly for those with conditions such as diabetes, 5 arrhythmias, 6 pre-eclampsia 7 and for the elderly. 8 Since its proposal in 2001, various hybrid devices 9,10 have been manufactured and validated. These devices provide a mercury-free, electronic pressure display that enables manual auscultatory BP measurement through the simulation of an aneroid display (Accoson Green-light, 11 A.C. Cossor & son Ltd., Essex, UK), a falling mercury column (A&D UM-101, 12 A&D Company Ltd., Tokyo, Japan), or a large numeric digital LCD (liquid crystal display) (Rossmax Mandaus II, Rossmax International Ltd., Taipei, Taiwan, 13 PMS Mandaus, 14 PMS Instruments Ltd., Berkshire, UK).…”
Section: Introductionmentioning
confidence: 99%